EXTRACTION OF ANTHOCYANIN FROM MANGOSTEEN PEEL: VARIATIONS OF TEMPERATURE, CONCENTRATION OF CITRIC ACID AND SOLID-LIQUID RATIO - Silvia Silvia; Reviana Inda Dwi Suyatmo; Tiara Nur Azizah; Syifa Aliya; Mutiara Rachma Fajria (Chemical Engineering Journal Storage (CEJS), 2026)
Mangosteen peel (Garcinia mangostana L.) is an agricultural residue that contains a rich source of bioactive substances, particularly anthocyanins. Mangosteen peel weighs 60% of the weight of the fruit, so it has the potential to be used as a natural dye because the amount of peel waste is greater than the fruit flesh consumed. Although mangosteen peel contains a substantial number of anthocyanins, its potential remains underexplored due to ineffective extraction techniques. The process of extracting anthocyanins from mangosteen peel is influenced by several variables, such as temperature, citric acid concentration in ethanol, and the ratio of solid to liquid. This research aims to evaluate how temperature, citric acid concentration in ethanol, and solid-to-liquid ratio influence the efficiency of anthocyanin extraction from mangosteen peel. Based on the research results, as the temperature increases, the anthocyanin levels decrease. The highest anthocyanin content was obtained at an extraction temperature of 25℃ of 105.16 mg/L. As the percentage of citric acid increases, the anthocyanin content also increases. However, there was a decrease in anthocyanin levels at a citric acid percentage of 1.5% so that the optimum value was obtained at 1% citric acid with an anthocyanin content of 98.19 mg/L. As the ratio of mangosteen peel powder and solvent increases, the anthocyanin content decreases. This could be caused by the volume of solvent increasing while the mass of mangosteen peel powder remains the same so that no more anthocyanins can be extracted as the solvent is added.